Klasifikasi impaksi gigi molar ketiga melalui pemeriksaan radiografi sebagai penunjang odontektomi - Yurika Ambar Lita; Indra Hadikrishna (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: Odontectomy is a common procedure in the extraction of third molars. Assessment of the difficulty level of extraction of third molars can be evaluated based on the classification of impaction. This article aims to discuss how the classification of impaction in third molars evaluates the difficulty of odontectomy treatment through radiographic examination. Literature Review: Literature search was carried out from various electronic databases with article inclusion criteria that discussed the validity of third molar impaction classification through radiography. Conclusion: Based on the findings of this review, it can be concluded that various stratified classifications are suggested as index that can be considered and recommended in the assessment of the difficulty level of third molar odontectomy.